A review on advanced nanofiber technology for membrane distillation. (January 2019) - Yalcinkaya, Fatma
The importance of the nanofiber webs increases rapidly due to their highly porous structure, narrow pore size, and distribution; specific surface area and compatibility with inorganics. Electrospinning has been introduced as one of the most efficient technique for the fabrication of polymeric nanofibers due to its ability to fabricate nanostructures with unique properties such as a high surface area and porosity. The process and the operating parameters affect the nanofiber fabrication and the application of nanofibers in various fields, such as sensors, tissue engineering, wound dressing, protective clothes, filtration, desalination, and distillation. In this review, a comprehensive study is presented on the parameters of electrospinning system including applications. More emphasis is given to the application of nanofibers in membrane distillation (MD). The research developments and the current situation of the nanofiber webs in MD are also discussed.